Supercontinuum generation in highly birefringent dual-mode fiber - Jozwik, Michalina; Holdynski, Zbigniew; Napierala, Marek; Budnicki, Dawid; Ziolowicz, Anna; Mergo, Paweł; Nasilowski, Tomasz (Photonics Letters of Poland, 2016)
We present experimental analysis of supercontinuum generation obtained for highly birefringent and highly nonlinear dual-mode fiber. A specific difference between the zero dispersion wavelength of fundamental mode and higher order mode in such fiber gives possibility of a normal and an anomalous dispersion regime pumping, depending on the mode, which is excited. The nonlinear effects responsible for the generation of broadband spectrum of the light are analyzed when the fiber is pumped by the pulse pump source operating at the wavelength of 1064nm. Full Text: PDF References J. M. Dudley, G. Goëry, and C. Stéphane, "Supercontinuum generation in photonic crystal fiber", Reviews of modern physics 78(4), 1135 (2006). CrossRef J. C. Knight, and D. V. Skryabin, "Nonlinear waveguide optics and photonic crystal fibers", Opt. Express, 15(23), 15365-15376 (2007). CrossRef Z. Holdynski et al., "Experimental study of dispersion characteristics for a series of microstructured fibers for customized supercontinuum generation", Opt. Express 21(6), 7107-7117 (2013). CrossRef M. Napierala et al., "Influence of photonic crystal fiber manufacturing inaccuracies on supercontinuum generation", SPIE Photonics Europe, International Society for Optics and Photonics, p. 91361M-91361M-6 (2014). CrossRef J. M. Dudley, and J. R. Taylor: Supercontinuum generation in optical fibers (Cambridge University Press, 2010). CrossRef P. Falk, M. H. Frosz, and O. Bang, "Supercontinuum generation in a photonic crystal fiber with two zero-dispersion wavelengths tapered to normal dispersion at all wavelengths", Opt. Express 13(19), 7535?7540 (2005). CrossRef A. Hartung, A. M. Heidt, and H. Bartelt, "Design of all-normal dispersion microstructured optical fibers for pulse-preserving supercontinuum generation", Opt. Express, 19, 7742-7749 (2011). CrossRef B. Jinendra, K. Ranka, R. S. Windeler, and A. J. Stentz, "Optical properties of high-delta air?silica microstructure optical fibers", Opt. Lett., 25, 796-798 (2000). CrossRef J. C. Knight et al., "Anomalous dispersion in photonic crystal fiber", IEEE Photon. Technol. Lett. 12(7), 807?809 (2000). CrossRef T. Tenderenda et al., "Fibre Bragg Gratings written in highly birefringent microstructured fiber as very sensitive strain sensors", SPIE Photonics Europe, International Society for Optics and Photonics, p. 84260D-84260D-8 (2012). CrossRef T. Tenderenda et al., "Highly birefringent dual-mode microstructured fiber with enhanced polarimetric strain sensitivity of the second order mode", Opt. Express, 20, 26996-27002 (2012). CrossRef K. Stepien et al., "Fiber Bragg gratings in hole-assisted multicore fiber for space division multiplexing", Opt. Lett., 39, 3571-3574 (2014). CrossRef http://www.lumerical.com/tcad-products/mode/. DirectLink